2016
DOI: 10.1007/s00264-016-3329-6
|View full text |Cite
|
Sign up to set email alerts
|

Silver-coated endoprosthetic replacement of the proximal humerus in case of tumour—is there an increased risk of periprosthetic infection by using a trevira tube?

Abstract: Level 3, retrospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…2 However, within each selected patient population and anatomical localization, silver-coated implants have consistently shown lower infection rates in comparison to other implants 18,[25][26] and our results corroborate these findings in the setting of an independent institution with longer follow-up from previous smaller patient series. 4,5,20,22,23 The overall 12 % infection rate of the presented study is almost identical to the previously published series of mixed primary resections with revision arthroplasty where Glehr et al 27 reported an infection rate of 12.5 % among 32 patients who had been treated with MUTARS® silver-coated endoprostheses and Wafa et al 18 reported an overall postoperative infection rate of 11.8 % in the silver-coated group of 85 Agluna-Stanmore Implants. Likewise, Schmolders et al 4 had to perform revision operations due to infection in 10 % of their implanted silver-coated MUTARS® endoprostheses after a median follow-up of 24 months for primary or metastatic oncological patients.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…2 However, within each selected patient population and anatomical localization, silver-coated implants have consistently shown lower infection rates in comparison to other implants 18,[25][26] and our results corroborate these findings in the setting of an independent institution with longer follow-up from previous smaller patient series. 4,5,20,22,23 The overall 12 % infection rate of the presented study is almost identical to the previously published series of mixed primary resections with revision arthroplasty where Glehr et al 27 reported an infection rate of 12.5 % among 32 patients who had been treated with MUTARS® silver-coated endoprostheses and Wafa et al 18 reported an overall postoperative infection rate of 11.8 % in the silver-coated group of 85 Agluna-Stanmore Implants. Likewise, Schmolders et al 4 had to perform revision operations due to infection in 10 % of their implanted silver-coated MUTARS® endoprostheses after a median follow-up of 24 months for primary or metastatic oncological patients.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, the results in revision arthroplasty patients are difficult to analyse within or between different centres due to different diagnostic methods of infection (e.g., sonication), perioperative antibiotic regiments, number of previous surgical procedures and pre-existing infections. All these limitations were also present in all other recent studies of this topic [1][2][3][4][5][6][19][20][21][22][23][24] where the infection-rate variability of silver-coated implants was larger between different patient populations (primary resection, metastases, revision, previous infection) and anatomical localizations than between different implant types (silver-coated vs. non-coated). 2 However, within each selected patient population and anatomical localization, silver-coated implants have consistently shown lower infection rates in comparison to other implants 18,[25][26] and our results corroborate these findings in the setting of an independent institution with longer follow-up from previous smaller patient series.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Alternatively, when the rotator cuff needs to be resected, attachment tubes made from polyethylene terephthalate (PET) are available [35]. In 2016, Schmolders et al showed that a higher infection rate was not observed in their population of 30 patients with a proximal humerus replacement when treated with an attachment tube, even if the patients were receiving immunosuppression therapy [36]. In view of the high risk of infection with the use of megaprostheses, silver-coated versions are now available and should be used [37].…”
Section: Wide Resectionmentioning
confidence: 99%
“…1 AP radiograph of the pelvis and both hips with fracture-risk osteolytic lesion of the proximal femur. with proximal humeral replacement techniques the use of a silvercoated modular tumor endoprosthesis in combination with a trevira tube represents a safe and reliable treatment option which is not associated with a statistically increased risk or periprosthetic infection [28]. In patients with proximal bone defects of the shoulder region, alloarthroplastic joint replacement by means of a shoulder prosthesis is often the only treatment option remaining.…”
Section: Upper Extremitymentioning
confidence: 99%